2021
DOI: 10.1007/s11239-021-02394-7
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic complications in 2928 patients with COVID-19 treated in intensive care: a systematic review

Abstract: A prothrombotic state is reported with severe COVID-19 infection, which can manifest in venous and arterial thrombotic events. Coagulopathy is reflective of more severe disease and anticoagulant thromboprophylaxis is recommended in hospitalized patients. However, the prevalence of thrombosis on the intensive care unit (ICU) remains unclear, including whether this is sufficiently addressed by conventional anticoagulant thromboprophylaxis. We aimed to identify the rate of thrombotic complications in ICU-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 59 publications
1
84
1
8
Order By: Relevance
“…There was a statistically significant higher incidence of severe thrombocytopenia, and a tendency towards higher rates of bleeding in the intermediate dose arm; complications that may limit the role of anticoagulation in reducing the thrombotic burden. One observation from this trial was that the incidence of venous thrombosis in the control arm, at 3.5%, was substantially lower that identified in the previously described meta-analysis, and requires further assessment in prospective studies [24].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…There was a statistically significant higher incidence of severe thrombocytopenia, and a tendency towards higher rates of bleeding in the intermediate dose arm; complications that may limit the role of anticoagulation in reducing the thrombotic burden. One observation from this trial was that the incidence of venous thrombosis in the control arm, at 3.5%, was substantially lower that identified in the previously described meta-analysis, and requires further assessment in prospective studies [24].…”
Section: Discussionmentioning
confidence: 62%
“…This compares to an overall incidence of thrombosis of 11.5% in 2505 non-ICU hospitalised patients, comprising PE (2.2%), DVT (2.0%), stroke (0.9%) and myocardial infarction (7.3%). In a meta-analysis of 2928 patients on ICU with COVID-19, our team identified a cumulative thrombotic incidence of 34% [24].…”
Section: Thrombotic Complications Of Covid-19 On the Intensive Care Settingmentioning
confidence: 99%
“…Remarkably, Grandmaison et al report a high VTE-incidence of 56% even in ICU patients receiving therapeutic anticoagulation [12]. A recent systematic review of 28 studies including a total of 2,928 patients with COVID-19 found that thrombotic complications were reported in 34% of ICU-managed patients, with DVT in 16.1% and PE in 12.6% of patients, despite anticoagulant thromboprophylaxis [17]. Studies adopting systematic screening for VTE with Duplex ultrasound reported a significantly higher incidence of venous thrombosis on the ICU compared to those relying on clinical suspicion (56.3% vs. 11.0%, p < 0.001) [17].…”
Section: On the Intensive Care Unit (Icu)mentioning
confidence: 99%
“…In the only reported case of SVT occurring during ICU stay, the presence of pharmacological prophylaxis of thrombosis was not reported. Previous research suggested that the incidence of thrombotic complications in ICU patients with COVID-19 infections is remarkably high despite anticoagulant therapy at standard prophylactic dose [49] . Notwithstanding this, recent evidence on patients admitted to the ICU with COVID-19 showed that intermediate-dose prophylactic anticoagulation did not result in a significant difference in the primary outcome of a composite of adjudicated venous or arterial thrombosis, treatment with extracorporeal membrane oxygenation, or mortality within 30 days [50] .…”
Section: Discussionmentioning
confidence: 99%